Distributional Characteristics of Termites (Insecta: Isoptera) among Different Types of Habitats in Dak Lak Area - Quang, Nguyen Van; Huy, Nguyen Quoc; My, Nguyen Thi (VNU Journal of Science: Natural Sciences and Technology, 2016)
Abstract: The sampling was followed the method of rapid biodiversity assessment of termites by Jones and Eggleton (2000), and have conducted for the first time in Dak Lak. In the studied natural habitats both termite richness and relative abundance were decreased from primary forest to secondary forest then to savanna (20 species → 11 species → 9 species) and (56 encounters → 30 encounters → 27 encounters) respectively. In the tree plantations, both richness and abundance in pine plantation higher than those in rubber plantation (13 species and 8 species) and (62 encounters and 53 encounters) respectively. The litter feeders dominated in habitats with high human impacts (secondary forest and savanna), while the soil feeders dominated in tree plantations or in rehabilitated ecosystem (pine plantation and rubber plantation). Beside human impacts on habitats, soil moisture played a very important role in the distribution of termites in the studied habitats. Keywords: Termite distribution, habitat, Dak Lak.